FASILITAS OBJEK WISATA BUKIT INDAH SIMARJARUNJUNG KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Damanik, Chesia Glora Bestari; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Currently Bukit Indah Simarjarunjung become one of the favorite touristattractions in North Sumatra Province. This object is very crowded visited by tourists,but the level of tourist visits does not match with facilities provided. Because of that Theaims of this study are to determine (1) The facilities condition of object tourism in BukitIndah Simarjarunjung District Simalungun, (2) the management of of object tourism inBukit Indah Simarjarunjung District Simalungun. The design of this study is qualitativedescriptive. The subject of this research is key informan namely, the cheft manager ofBukit Indah Simarjarunjung, and additional informants are visitors. The techniques ofdata collection are observation, documentatuin, and interview. The result of this studysare the facilities conditition of object tourism in Bukit Indah Simarjarunjung DistrictSimalungun is good enough, but the facilities provided do not match the number oftourists who visit. The Planning of tourism object facilities is grouped into long-termand short-term planning. The Organizing has not been formed by the manager. Theactuating should continue to control the existing facilities, so that in case of damage isimmediately corrected. The Controling is not good because only supervised by themanager, lack of attention and move from the government.Keywods : Facilities, Management, Bukit Indah Simarjarunjung